PENGARUH DUKUNGAN MANAJEMEN PUNCAK DAN BUDAYA ORGANISASI TERHADAP PEMANFAATAN SISTEM INFORMASI AKUNTANSI - Sunarti Narti (ITB AAS INDONESIA Surakarta, 2021)
This study aims to find out if peak management support can influence the utilization of accounting information systems and whether organizational culture can also influence the utilization of accounting information systems. This research was conducted using quantitative approach and using primary data in the form of questionnaires. Questionnaire using google form and distributed using whattapp application. This study used 87 samples, with respondents users of accounting information systems in klaten district. Sampling techniques use purposive sampling techniques. The results of this study showed that the support of top management has no effect on the utilization of accounting information systems, but the culture of the organization has an influence on the utilization of accounting information systems.